Sunitinib-Induced Acute Liver Failure - Aqsa, Anum (Case Rep Gastroenterol, 2021)
Drug-induced liver injury is an uncommon but life-threatening entity. Sunitinib is a tyrosine kinase inhibitor used for advanced and imatinib-refractory gastrointestinal stromal tumors. It causes transient elevation in liver enzymes. The incidence of fatal acute liver failure is rare. Five cases of sunitinib-induced acute liver injury have been reported in the literature thus far. We present a case of fatal acute liver failure and cardiomyopathy within 2 weeks of sunitinib therapy initiation for advanced pancreatic neuroendocrine carcinoma. We believe our case is unique due to the rarity of its presentation. It highlights hepatotoxicity as a potentially fatal side effect of sunitinib therapy.